ADAPTABILITAS KARIR PESERTA DIDIK BERDASARKAN STATUS EKONOMI KELUARGA (Studi Deskriptif terhadap Peserta Didik Kelas XI SMA Negeri 1 Subang Tahun Ajaran 2020/2021) - Muhammad Yusuf Firdaus, - (2020)
Teenagers should have Career Adaptability to gain the growth tasks in selecting and preparing their career. Senior High School students are in the phase of teenagers who are facing the selection or designing their career to prepare themselves to cope with their job or their career decision. The purpose of the research is to get a description of career adaptability of the Students of SMA Negeri 1 Subang Grade XI, Class of 2020/2021. The description of career adaptibility is based on their Family Economic Satus. The reserch is conducted using quantitative approach and deccriptive method. The data measurement is the questionnaires in the form of scales adopted from Career Adapt-Abilities Scale (CAAS) developed by Savickas dan Porfeli (2012). Population and sample of the research are 304 Students of SMA Negeri 1 Subang Grade XI, Class of 2020/2021. The result of the research are : (1) Generally, career adaptability of the Students of SMA Negeri 1 Subang Grade XI, Class of 2020/2021 is in adaptive category. (2)the economic status of the students family do not influence their career adaptability. Recommendation for BK teacher of SMA Negeri 1 Subang is to be able to design the strategies of basic service of career guidance for the students to facilitate them in improving their career adaptivity. Keywords: career adaptability, students, and family economic status.